Judicial Review and Its Role in Safeguarding Constitutional Rights in Modern Democracies - Satria, Rahmad (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the role of judicial review in safeguarding constitutional rights within modern democracies, using a literature review approach. Judicial review serves as a critical mechanism for ensuring that laws and government actions comply with constitutional principles. By empowering courts to evaluate the constitutionality of legislation, judicial review protects individual rights and prevents the abuse of governmental power. The research explores the evolution of judicial review, its various models, and its impact on the balance of power between different branches of government. The findings highlight the significance of judicial review in upholding democratic values, such as the rule of law, separation of powers, and the protection of minority rights. Through case studies from different democratic systems, the study analyzes the strengths and limitations of judicial review in addressing constitutional challenges. While judicial review has proven essential in safeguarding rights, it also faces criticisms related to judicial activism and its potential to undermine legislative authority. This research concludes that, despite these challenges, judicial review remains a fundamental pillar in the defense of constitutional rights in modern democracies, providing a necessary check on legislative and executive actions to preserve democratic integrity.